EVALUATION OF MANAGEMENT INFORMATION SYSTEMS FOR PHARMACEUTICAL INVENTORY CONTROL AT THE HOSPITAL - Putri, Diah Kartika; Pribadi, Prasojo; Merari P, Jason (Universitas Aisyah Pringsewu, 2024)
Hospital X is one of the hospitals in Lampung that has implemented management information systems for pharmacy since 2016, has not yet been evaluated, and there are several obstacles, such as the absence of warnings for out-of-stock drugs and drug procurement planning is still calculated manually. This research was a descriptive study with a cross sectional approach to the management information system of pharmaceutical inventory control. This research data comes from the distribution of the DeLone and McLean questionnaires and the results of structured interviews to support system development. Based on calculations used a predetermined formula, it is said that the level of respondents' satisfaction with management information systems drug inventory control is in the medium category, but is still very far from the high satisfaction category, so further interviews are needed. After developing a pharmaceutical inventory control management information systems, there were 18 participants from pharmacy participated in training and self-testing for eight days. Based on the research that has been done, it can be concluded that the level of the respondent's satisfaction category has increased its variables, the satisfaction variable has a perception of satisfaction in the medium category of 100% and the high category of 0%, but after developing a pharmaceutical inventory control system, the satisfaction level of respondents in the high category has increased was 27.78%, so the development of a control management information system needs to be done.